ANALISIS DAERAH BINTIK MANIS PADA PERANCANGAN RAKET BULUTANGKIS - Bagus Budiwantoro; I Wayan Suweca; Roby C. M Sibuea (Mesin, 1998)
One method to increase badminton racket performance is by improving individual player's racket. For this purpose, two measurements are necessary, i.e. (1) the racket 's location of sweet spot that is inherent due to its manufacturing process and (2) the players